Outcomes study between femtosecond laser-assisted cataract surgery and conventional phacoemulsification surgery using an active fluidics system - Hida WT (Dove Medical Press, 2017)
Wilson Takashi Hida,1–4 Patrick Frenzel Tzelikis,1–3 César Vilar,1,2 Mario Augusto Pereira Dias Chaves,1,2,5 Antônio Francisco Pimenta Motta,1–3 Pedro Carlos Carricondo,1–3 Bruna Vieira Ventura,1,2,4,6 Renato Ambrosio Junior,1–3 Walton Nosé,1,2,4 Milton Ruiz Alves1–3 1Department of Cataract of Brasília Ophthalmology Hospital (HOB), Brasília, Federal District, 2Renato Ambrosio Research Center (CEORA), Brasília, Federal District, 3Department of Ophthalmology of São Paulo University School of Medicine, (FM-USP), São Paulo, 4Department of Ophthalmology of São Paulo Federal University (UNIFESP) School of Medicine, São Paulo, 5ProVisão Hospital, João Pessoa, Paraíba, 6Pernanbuco Eye Hospital (HOPE), Recife, Pernambuco, Brazil Purpose: The purpose of this study was to compare intraoperative parameters between femtosecond laser-assisted cataract surgery (FLACS) and conventional phacoemulsification using Centurion® Vision System with Active Fluidics. Setting: This study was performed at Brasília Ophthalmologic Hospital, Brasília, Federal District, Brazil. Patients and methods: This was a prospective randomized comparative study. Patients with the diagnosis of cataract and surgical extraction programmed were divided into two groups: conventional phacoemulsification and FLACS. Intraoperative data were collected and submitted for statistical analysis. Results: A total of 400 eyes were enrolled, 200 in each group. There were no surgical complications. Groups were statistically equivalent in age and nucleus density. Cumulative dissipated energy and torsional time were significantly reduced in the FLACS group. Conventional surgery had less fluid usage, total case time and aspiration (ASP) time. Conclusion: FLACS with Active Fluidics System can reduce the ultrasound energy use during cataract surgery, in spite of increasing case time, fluid usage and ASP time. Keywords: FLACS, ultrasound, aspiration